Anticonvulsant and behavioral effects of muscimol in immature rats - Mareš, Pavel; Tichá, Kateřina; Mikulecká, Anna (Brain research, 2014)
Potentiation of GABAergic inhibition is a mechanism of action of many antiepileptic drugs. The potential use of an agonist of GABAA receptors, muscimol, as an antiepileptic drug was studied in immature rats by assessing anticonvulsant activity and side effects on motor activities. Anticonvulsant action was tested in two models of seizures (pentetrazol-induced convulsions and cortical epileptic afterdischarges). Off target effect on motor performance was assessed in a battery of tests and in the open field in three age groups (12-, 18- and 25-day-old rats). Muscimol was administered in doses from 0.1 to 1mg/kg i.p. Only the 1 mg/kg dose exhibited marked anticonvulsant effect against pentetrazol-induced convulsions in 12- and 18-day-old rats, proconvulsant effect was observed in the second model in 18- and 25-day-old rats as prolongation of afterdischarges. Even the 0.5 mg/kg dose suppressed spontaneous locomotion and heavily compromised motor performance. The effect on motor activity was marked in the youngest group and decreased with age. Due to the low anticonvulsant potency and serious side effects, systemic administration of a competitive agonist of GABAA receptors in immature animals is not a promising strategy for new anticonvulsants.
Keywords: Pentylenetetrazole; Animals; Epilepsy; vztah mezi dávkou a účinkem léčiva; Rats, Wistar; Seizures; Age Factors; Neuropsychological Tests; Electroencephalography; Anticonvulsants; Muscimol; pohybová aktivita; GABA-A Receptor Agonists; věkové faktory; neuropsychologické testy; pentylentetrazol; Exploratory Behavior; antikonvulziva; mozek; stupeň závažnosti nemoci; muscimol; agonisté receptorů GABA-A; epilepsie; Dose-Response Relationship, Drug; Male; modely nemocí na zvířatech; Brain; Disease Models, Animal; Motor Activity; pátrací chování; zvířata; mužské pohlaví; Severity of Illness Index; elektroencefalografie; záchvaty; potkani Wistar